1999
DOI: 10.1007/bf03402075
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate Switches the Pattern of Chemokine Secretion by Intestinal Epithelial Cells through Histone Acetylation

Abstract: Background: Butyrate, a fermentation product of intestinal bacteria, modifies chromatin structure through histone acetylation, thereby altering gene transcription. IL-8 and MCP-1 are chemokines, expressed by intestinal epithelial cells, which attract neutrophils and monocytes, respectively. We hypothesized that butyrate may alter 11-8 and MCP-1 expression by intestinal epithelial cells through histone acetylation. Materials and Methods: IL-8 and MCP-1 expression was measured by ELISA and RNA transfer blots. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
69
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 34 publications
(25 reference statements)
7
69
1
Order By: Relevance
“…These results indicate that the up-regulation of IL-8 by butyrate alone may involve an NF-kB-independent mechanism. This has been previously reported by Fusunyan et al, who showed that butyrate increased the production of IL-8 through histone acetylation [12]. Butyrate selectively induced histone acetylation at the Nod2 promoter but not at Nod1 or Tlr2.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…These results indicate that the up-regulation of IL-8 by butyrate alone may involve an NF-kB-independent mechanism. This has been previously reported by Fusunyan et al, who showed that butyrate increased the production of IL-8 through histone acetylation [12]. Butyrate selectively induced histone acetylation at the Nod2 promoter but not at Nod1 or Tlr2.…”
supporting
confidence: 83%
“…2009. 39: 3529-3537 Chung-Hang Leung et al Butyrate enhances IL-8 secretion mediated by IL-1b, bacteria, and yeast, whereas it inhibits NF-kB activation by TNF-a and phorbol ester [12][13][14][15][33][34][35][36]. Among its diverse activities, the suppression of NF-kB activity through HDAC inhibition is the most frequently studied anti-inflammatory effect of butyrate [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies reported that butyrate could both up-and down-regulate production of IL-8 (2-6). The up-regulatory effect may result from its chromatin remodeling action by inhibiting histone deacetylase (2). However, no satisfactory model is available to interpret its down-regulation of IL-8 expression.…”
mentioning
confidence: 99%
“…7,8) The exposure of IEC lines, including Caco-2, to butyric acid, a short chain fatty acid produced by bacterial carbohydrate fermentation in the mammalian intestine, 9,10) has been found to alter the cytokine secretion, NF-B activation, arachidonic cascade, cell cycles, cell differentiation and alkaline phosphatase activity of these cells. [11][12][13][14][15][16] We have previously shown that IEC-like Caco-2 cells cultured in a medium containing 10 mM butyric acid secreted interleukin-8 (IL-8/CXCL-8) in response to both non-pathogenic S. cerevisiae and the opportunistic pathogenic C. albicans.…”
mentioning
confidence: 99%